2018
DOI: 10.1002/msc.1245
|View full text |Cite
|
Sign up to set email alerts
|

Initial derivation of diagnostic clusters combining history elements and physical examination tests for symptomatic knee osteoarthritis

Abstract: Diagnostic clusters combining history elements and physical examination tests were able to support the differential diagnosis of SOA compared with various knee disorders without relying systematically on imaging. This could support primary care clinicians' role in the efficient management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…Therefore, for clinically “certain” knees, diagnostic abilities based on clinical data only should be considered as good enough, in contrast to clinically “uncertain” knees. Our results support expert recommendations and the results of previous studies [ 3 , 4 , 6 , 7 , 8 ], where diagnoses based on clinical findings were found to be reliable and where radiographs were deemed unnecessary for diagnosing typical KOA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, for clinically “certain” knees, diagnostic abilities based on clinical data only should be considered as good enough, in contrast to clinically “uncertain” knees. Our results support expert recommendations and the results of previous studies [ 3 , 4 , 6 , 7 , 8 ], where diagnoses based on clinical findings were found to be reliable and where radiographs were deemed unnecessary for diagnosing typical KOA.…”
Section: Discussionsupporting
confidence: 90%
“…The European League Against Rheumatism Recommendations (EULAR) reported that three symptoms (knee pain, morning stiffness less than 30 min and functional limitation) combined with three clinical signs (crepitus, restricted range of motion and bone enlargement) could predict 99% radiographic KOA [ 3 ]. Similarly, recent studies showed that clinical manifestations, such as knee pain, crepitus, joint line tenderness, bony swelling and pain on flexion/extension could be used for identifying radiographic KOA [ 4 , 5 , 6 ]. Current recommendations advise not to use imaging in patients with typical OA presentations, but these were mainly based on expert opinion [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having a diagnostic of knee OA was associated with a decreased probability of diagnostic discordance as well in our study. Knee OA may be easier to diagnose since older age of the patient is a good indicator of OA [ 26 ]. Having MRI results, which was associated with a higher probability of diagnostic discordance in both analyses, could be related to more complex traumatic injuries and reveal concomitant lesions, although this was not shown in our results.…”
Section: Discussionmentioning
confidence: 99%